2013
DOI: 10.1111/clr.12101
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bone marrow aspirates and concentrates on the early volume stability of maxillary sinus grafts with deproteinized bovine bone mineral – first results of a RCT

Abstract: An evident decrease in graft volume over the first 6 months of healing has to be expected irrespectively of graft composite. Neither BMA nor BMAC seem to have an evident impact. Overaugmentation seems recommendable in two-stage maxillary sinus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 18 publications
5
25
0
2
Order By: Relevance
“…The mean percentage of volume loss was 33.14% for the test group (DBBM + L‐PRF) and 36.71% for the control group (DBBM only). These variations in the volumetric changes were also observed in previous studies . Accordingly, previous studies have demonstrated that the mean volume reduction of DBBM in the maxillary sinus ranges from 15.2% to 21.5% .…”
Section: Discussionsupporting
confidence: 83%
“…The mean percentage of volume loss was 33.14% for the test group (DBBM + L‐PRF) and 36.71% for the control group (DBBM only). These variations in the volumetric changes were also observed in previous studies . Accordingly, previous studies have demonstrated that the mean volume reduction of DBBM in the maxillary sinus ranges from 15.2% to 21.5% .…”
Section: Discussionsupporting
confidence: 83%
“…It can also be stated that the respective bone substitute material has no negative effect on volume stability. These results confirm findings of a similar study performed by the same working group in which bone marrow aspirates (BMA) and concentrates (BMAC) were added to deproteinized bovine bone mineral (DBBM) in a split‐mouth design . This study showed that neither BMA nor BMAC improved the volume stability of the grafts after six months of healing .…”
Section: Discussionsupporting
confidence: 87%
“…Prospective randomized studies using a split‐mouth design with bilateral sinus augmentation to measure time‐dependent graft resorption three‐dimensionally have, to date, not been published for any material except DBBM + BMA and BMAC. However, taking all bias into consideration, the percentage decrease of volume in both groups – 15% in the control group and 18% in the test group – lies within the range of the above three‐dimensional‐based studies, with 14% for algae‐derived hydroxyapatite, 15.2% for DBBM + BMA, 21.5% for DBBM + BMAC, 25% for autogenous bone and 26% for DBBM alone …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Numerous studies have been published on bone graft stability based on two‐dimensional imaging techniques, demonstrating a significant decrease in augmented bone height within 6‐24 months after sinus lifting . Studies have also been reported on the three‐dimensional (3D) volume stability of these grafts . Although being numerous, these studies differ substantially regarding follow‐up time, method of evaluation, bone graft material, and surgical procedures.…”
Section: Introductionmentioning
confidence: 99%